Baseline Susceptibility Status of Florida Populations of Aedes aegypti (Diptera: Culicidae) and Aedes albopictus. Issue 5 (17th April 2020) - Parker, Casey; Ramirez, Daviela; Thomas, Carol; Connelly, C Roxanne
Abstract: Resistance to insecticides used to control mosquito vectors threatens the ability of mosquito-control organizations to protect public health. Aedes aegypti (Linnaeus) and Aedes albopictus (Skuse) are invasive species widely distributed throughout Florida and have been implicated in recent epidemics of Zika, dengue, and chikungunya viruses. Knowledge of the susceptibility status of these mosquito species to pyrethroid and organophosphate active ingredients (AIs) is needed to inform product selection and treatment decisions. The susceptibility of 37 Ae. aegypti and 42 Ae. albopictus populations from Florida was assessed in response to six pyrethroid and three organophosphate AIs using the CDC bottle bioassay method. Of all bioassays completed with a pyrethroid AI, 95% for Ae. aegypti and 30% for Ae. albopictus resulted in a resistant outcome. For organophosphate AIs, 31% of assays conducted for both species were classified as resistant. The highest frequency of susceptibility for both species was observed in response to the organophosphate AI, naled. Lambda-cyhalothrin was the only pyrethroid to result in a susceptible status for Ae. aegypti and also had the highest frequency of susceptibility for Ae. albopictus . Resistance was detected to every AI tested for both Ae. aegypti and Ae. albopictus, but there was a pronounced trend of pyrethroid resistance in Florida populations of Ae. aegypti . The results of this work provide evidence for the need to decrease reliance on pyrethroids and to implement different methods of control of Ae. aegypti in Florida.